GOVERNMENT COMMUNICATION STRATEGIES IN THE AGE OF SOCIAL MEDIA POLITICS - Sudarti Sudarti; Kaito Tanaka; Riko Kobayashi (Cognitionis Civitatis et Politicae, 2026)
Government communication strategies have undergone significant transformation with the advent of social media, changing how governments interact with their citizens. In an era where social media has become a primary platform for political discourse, governments are adopting new communication approaches to foster engagement, transparency, and public participation. This study aims to explore the effectiveness of government communication strategies on social media, comparing their impact in both democratic and authoritarian regimes. The research examines how different governments utilize social media platforms like Facebook, Twitter, and Instagram to convey messages, interact with the public, and influence political behavior. A qualitative research design was employed, utilizing content analysis and expert interviews across four countries: the United States, Brazil, the United Kingdom, and China. The findings indicate that democratic governments engage more successfully with the public through transparent, interactive posts, fostering higher levels of trust and participation. In contrast, authoritarian governments utilize social media primarily as a tool for broadcasting state-controlled messages with minimal public engagement. The study concludes that government communication strategies should prioritize transparency and interactivity to enhance public engagement and trust in democratic societies, while authoritarian regimes may benefit from adopting more participatory approaches to improve public communication.